2021
DOI: 10.1111/ijcp.14773
|View full text |Cite
|
Sign up to set email alerts
|

Infarct volume and outcome of cerebral ischaemia, a systematic review and meta‐analysis

Abstract: Background Multiple studies have evaluated the accuracy of infarct volume (IV) as a predictor of outcome in patients with ischaemic stroke; however, no study has systematically reviewed the results of these studies. Aim This systematic review and meta‐analysis aim to sum up the results of the studies evaluating IV as the prognostic criteria for patients with cerebral ischaemia. Methods Human studies that reported the infarction volume and any prognostic outcome in patients with ischaemic stroke were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Our study showed that FIV was associated with poor clinical outcome and is an independent predictor of futile recanalization, which is consistent with previous studies 33,34,35,36 . However, the optimal cutoff FIV value is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that FIV was associated with poor clinical outcome and is an independent predictor of futile recanalization, which is consistent with previous studies 33,34,35,36 . However, the optimal cutoff FIV value is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Patients were divided into two groups based on infarct volume (≤20 cm 3 vs. >20 cm 3 ) ( Meng and Ji, 2021 ) and time since stroke onset (≤14 days vs. >14 days) ( Kanekar et al, 2012 ). According to a meta-analysis of research on predictive factors in ischemic stroke, the infarct volume cut-point of 50 ml is sensitive in differentiating favorable and unfavorable outcomes ( Meng and Ji, 2021 ). On the other hand, restoration of blood–brain barrier, resolution of vasogenic edema, and cleaning up of necrotic tissue begin after 14 days ( Kanekar et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…[98][99][100] Final infarct volume post-AIS is a critical radiographic measure linked to functional outcomes and complications like malignant cerebral edema and herniation. 101 Although imaging in the hyperacute/acute setting may not accurately reflect final infract volume, ML applications on acute MRI sequences have predicted it with high accuracy (AUC: 0.88). 102 ML has also been applied to predict the progression of cerebral edema through automated volumetric analysis of cerebrospinal fluid, with a recent study achieving a 90% accuracy in forecasting malignant cerebral edema requiring surgical intervention or resulting in death.…”
Section: Ischemic Strokementioning
confidence: 99%